The government of Kutai Kartanegara Regency indicates that the problem of shrimp pond’s business production and profit has been going down and being stagnant in Muara Badak. It is caused by capital source i.e own capital, ponggawa, bank loan and government loan. And directly capital source influenced different of quantity, input and output cost. In fact, the performance of lending mechanism is inefficient. The objectives of this research were to analyze the effect and capital source conditio - Handayani Boa; Yusman Syaukat; Idqan Fahmi (Forum Pasca Sarjana, 2010)
The government of Kutai Kartanegara Regency indicates that the problem of shrimp pond’s business production and profit has been going down and being stagnant in Muara Badak. It is caused by capital source i.e own capital, ponggawa, bank loan and government loan. And directly capital source influenced different of quantity, input and output cost. In fact, the performance of lending mechanism is inefficient. The objectives of this research were to analyze the effect and capital source condition and lending mechanism of capital source to production and profit. Econometrics approach was used to solve the problem through production and profit function. OLS and IPA were applied in this research. The result of estimated parameter and perception of fish farmer related to lending mechanism were used as policy implication. The result showed that capital loan from ponggawa, bank, and government were used only as working capital and the mechanism of capital loan from ponggawa was better than the other. It was caused by easier requirement and procedure application for lending is better facility and its services, free of charge lending mechanism and relatively clearance time of credit. Production rate of fish farmer who related to ponggawa were lower than the other. However, profit rate of fish farmer who related own capital were higher than the other. Key words: capital source effect, shrimp pond production, Muara Badak, Kutai Kartanegara